COMPASSIONATE TEACHING IN RICHARD LAGRAVANESE FREEDOM WRITERS - Kesita Tumbel; Nurmin Samola; Merlin Maukar (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This study aims to reveal how the main character in the film “Freedom Writers” by Richard La Gravanese teaches and educates her students who are full of racism with compassion. This study uses a qualitative research method because the authors collect data in the form of film scripts from Freedom Writers to be processed into a study. The author also uses a psychological approach and uses the theory of Muhtadi, and Maman Abd Jahlil who supports this research because it studies how to understand and study motives from the side of human psychology. The results of this study indicate that the main character in the film Freedom Writers uses various methods and goes through various processes to unite her students in her class which are full of racism. The result of this research, we can make an example that work as a teacher not only focuses on the students score, but also the value of life is no less important that must be given to students with compassionate.